American hegemony at a critical juncture, lessons from history's great powers - Patel, Ketan; Hansmeyer, Christian; Desai, Nandan; Ajit, Aditya (Frontiers in Political Science, 2025)
IntroductionAt the 2024 election, Americans faced a pivotal choice about their nation's global trajectory, amid intensifying debate over the future of U.S. hegemony. This study investigates whether the United States is experiencing a phase of hegemonic decline, signaling the end of its era as the world's leading great power, or whether its power can persist or even be revitalized.MethodsTo evaluate this, we employ a mixed-methods approach. We use quantitative modeling to analyze historical power lifecycles of previous hegemons, identifying inflection points and estimating the potential end dates of U.S. dominance. In parallel, we use qualitative analysis of recurring historical markers of decline - such as strategic overreach, domestic polarization, and eroding global legitimacy - to assess their presence in current U.S. conditions.ResultsOur quantitative model projects potential turning points in American global primacy between 2032 and 2067. The qualitative analysis reveals that the United States currently exhibits several key recurring features of great-power decline, including internal division, weakened alliances, reduced moral authority, and challenges from rising powers with competing rule-setting ambitions.DiscussionWhile the United States maintains significant multidimensional strengths, these findings suggest that it may be transitioning into a phase of relative or systemic decline. This framework offers a foundation for further study into the drivers, agents, and timing of hegemonic transition, as well as how U.S. administrations may shape the durability or erosion of American leadership in the evolving international order.